A cross-sectional investigation of factors influencing mpox vaccine hesitancy for students in Southwest China - Xiu Yang; Xuetao Yang; Wenyi Jiang; Na Luo; Yibo Hu; Ya Yang; Xidan Yang; Lingli Hou; Jingjing Zhang; Congxia Hu; Jihui Lin (Human Vaccines & Immunotherapeutics)
From July to September 2023, China reported over 1, 400 confirmed cases of mpox transmitted mainly through sexual contact between males. Meanwhile, the percentage of men who have sex with men at universities in southwestern China is increasing every year, which is likely to lead to a potential spread of mpox on campuses. Vaccination is an effective preventive measure against infectious diseases, this study examined the willingness of university students in Southwest China to receive the mpox vaccine and analyzed the factors influencing their decision. A cross-sectional survey was conducted among 7311 university students from 10 universities in Southwest China between August 13 and September 1, 2023. The survey revealed a hesitancy rate of 56.13% toward the mpox vaccine, with the most common reason being concerns about vaccine safety (1407/4104, 34.29%). Univariate analysis identified 13 variables that significantly differed between the vaccine acceptance and vaccine hesitancy groups. Multivariate logistic regression analyses indicated protective factors for vaccine hesitancy, such as sexually transmitted diseases, previous knowledge about mpox, frequent information about mpox, people can get reinfection of mpox, and worries about mpox endemic in China. Additionally, the confidence and convenience dimensions in the 3Cs model were identified as risk factors for mpox vaccine hesitancy. This study found a high rate of vaccine hesitancy among university students in Southwest China regarding the mpox vaccine. Collaboration between university and healthcare departments is recommended to address mpox vaccine hesitancy among college students, thereby promoting their willingness to receive the mpox vaccine.